Evaluation of the potential of Stichopus Herrmanni extract in inhibiting cervical cancer cell proliferation - Irena Ujianti; Bety Semara Lakhsmi; Zahra Nurusshofa; Wawang S Sukarya (Elsevier, 2024)
Background: Sea cucumbers, particularly Stichopus herrmanni, are known for their medicinal value in Asian traditional medicine owing to the abundant presence of saponins, terpenoids, and phenols. Investigations on these bioactive compounds have revealed their cytotoxic propensity against various cancer cell lines, indicating their therapeutic potential. However, limited research exists on the potential application of sea cucumber extracts specifically in cervical cancer. Purpose: This study aimed to identify the bioactive components of Stichopus herrmanni extract, determine their association with potential targets in cervical cancer, and evaluate their cytotoxic effects on cervical cancer cells. Study Design: This experimental study employed both in vitro and in silico methods to evaluate the potential cytotoxic effects of Stichopus herrmanni extracts on cervical cancer cells. Methods: Liquid Chromatography-Mass Spectrometry (LC-MS) was used to identify and quantify the bioactive constituents of Stichopus herrmanni crude extract. An in silico approach was used to identify the active components, potential targets, and signaling pathways of the extract. Furthermore, the MTT assay was used to determine the cytotoxicity of the extract. Results: LC-MS analysis identified the presence of rengyol, eucommiol, ganoderic acid, and 6-isoinosine in the extracts. An in silico study based on structural analysis identified ganoderic acid and isoinosine as crucial active components capable of regulating majority of the targets associated with cervical cancer. Overlapping targets, namely, CASP3, CAT, FASLG, IL24, TP53, TP53BP1, ALB, BDNF, and COX2 between cervical cancer and the extract highlighted new therapeutic prospects for cervical cancer following protein-protein interaction network screening. The in vitro cytotoxic effects of the extracts were established in HeLa cells. Conclusion: Research indicates that Stichopus herrmanni may be a valuable source of bioactive compounds with potential applications in the treatment of cancer and the induction of apoptosis